Subjective-Objective-Subjective: The Science Of Propaganda - Bain, Jonathan (Department of Private Law, 2020)
This thesis discusses the following: 1. That, while advertising practitioners employ various levels of scientific endeavour (particularly strategic insight development, but also research, demographic data collection, and other objective tools of the trade), its final output is ultimately nonscientific, i.e. subjective creative ideation. (In this way, advertising is not dissimilar to the classic ‘art' of propaganda.) 2. That, for reasons of business necessity, creative ego and a latent form of ‘inferiority complex' the advertising industry describes its work in presentations to more scientifically-orientated clients as a more scientific proposition. 3. That, in contrast, as evidenced by the physical production process of the advertising idea (post the client presentation) – as well as in industry texts, award ceremonies, and selected case studies – advertising practitioners effectively acknowledge the subjective nature of their work. 4. That further evidence of this scientific ‘terministic screen' (Burke 1950, pp. 26-27) is also revealed in the failure of some television commercials to profitably ‘connect' as intended with an audience – thus undermining claims to the objective approach that preceded these commercials. 5. That, possibly, as is implied in at least one ethnographic case study, not even clients are necessarily convinced by advertising science: the ‘screen' may be a two-way mirror. 6. That there is, more broadly, a constant dialectic between right-brained creativity and the left-brained business project. 7. That this tension is a microcosm of the capitalist enterprise, and, in an increasing number of present examples, is perversely reflected in the advertising industry's output as anti-capitalist brand messaging. 8. That it is possible to think of advertising as a sub-set of a more consumer-orientated ‘design'. 6 9. That, admittedly within limited confines of my research, there is a tantalising indication that, generally, advertising artefacts were historically more logos-led, are currently more pathos-led, and may in future benefit from a more ethos-led orientation.